PRIVASI PADA PEKARANGAN SEBAGAI RUANG TERBUKA PRIVAT PERKOTAAN DI KAWASAN HUNIAN JERON BETENG KRATON YOGYAKARTA - , NOVA PURNAMA LISA; , Dr. Ir.Ahmad Sarwadi, M. Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Privacy is being understood as controlling capability by someone or group in implementing their interactions to other people. Privacy could help someone or group to arrange their personal space, whether to be nearer or away. Privacy is always needed by anybody, anytime, and anywhere, to gain a sense of comfort and secure when doing activities, including when they are in home garden as a private open space. Privacy is required interaction level or openness by someone in a given condition or situation. In the study of environment and behavioural architecture, home garden is not merely considered as outer side of a house, but also determined by other factors when arranging its inner space, which are, culture, religion, spatial, and behaviour itself. Therefore, a study with specific and clear context on privacy and home garden is needed to rich the treasure of behaviour and environmental architecture. This research is conducted by using case study paradigm with qualitative method. This research is using inductive qualitative approach by exploring or digging the finding and, then, description. Digging finding from home garden of Demang which are a middle class bureaucrat (abdi dalem) in dwelling area at Jeron Beteng Kraton Yogyakarta. Observed research sample consists of ten demangâs houses, and focused the importance of home garden privacy as a private open space in order to satisfying the privacy needed by its owner. Component of analysis consists of existing condition of demangâs home garden which includes several identifications to answer the questions in this research. To see how the pattern was formed the effort to satisfy the privacy and correlation between both factors. The results show that there are two types of home garden in demangâs houses, that is, extended family and nuclear family. Each type represents the pattern of formed home garden space, which consists of five home garden pattern spaces. There are eight efforts/attitudes in satisfying the need of privacy at extended family home garden and five efforts/attitudes in satisfying the need of privacy at nuclear family home garden. There are very significant and significant correlation between formed home garden patterns and the efforts of its owner to satisfy their privacy